Photocatalytic degradation of oily wastewater by ZrO2(Er3+)/TiO2 composite photocatalyst. Issue 1 (October 2020) - Liu, Yunqing; Feng, Dan; Wang, Xinglei
Abstract: Photocatalyst/polypropylene ball which can float on the water is prepared through coupling agent method, and the photocatalyst is the ZrO2 (Er 3 +)/TiO2 which is fabricated by co-precipitation. The diesel and crude oil degrading experiments are made with the floating photocatalyst and powder photocatalyst. After 8 hours illuminating in visible light, the removal rate of diesel in float experiment can reach 98%, however the rate in ZrO2 (Er 3 +)/TiO2 powder experiment is 68%. The removal rate of crude oil in float experiment is more than 96%, which is much higher than the removal rate of 39% of crude oil in ZrO2 (Er 3 +)/TiO2 powder experiment.